The Health Students’ Perception of Online Education amid the Pandemic - Ahmet Baytak (Research in Social Sciences and Technology- OpenED Network, 2022)
The recent Covid-19 pandemic has changed the lifestyles throughout the World. This study aims to investigate the health students’ perception of online education. The field of health requires practical education. Indeed, online education has a different concept. Thus, the health students’ perceptions draw attention especially during the hard time of pandemic. This quantitative study was conducted with 581 students studying a field of health in Turkey. The data from an online survey was analyzed with Kruskal Wallis and Mann-Whitney U tests. The results show that health students’ perception on online education was found to be medium. Even though some are favor of online education with some points, some see this type of learning platform not suitable for their fields. There was no significant difference between the perception of female and male students. The students’ perception differences were found statistically significant by departments, classes, watching lessons live, having technology difficulties and using different device to access to online education. These findings confirmed that the sudden shift to online education made a different experience for health students. The research concludes with suggestions to design online education for any unexpected pandemic.